FORUM MŁODYCHPostinfarction ventricular septum rupture complicated with cardiogenic shock, requiring reoperation - Zimoch, Wojciech; Pawluś, Aleksander; Sokolski, Mateusz; Sukiennik-Kujawa, Małgorzata; Kustrzycka-Kratochwil, Dorota; Gemel, Marek; Skiba, Jacek; Banasiak, Waldemar; Jankowska, Ewa Anita; Ponikowski, Piotr (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
Ventricular septal rupture (VSR) is a rare, but always a life- threatening complication of acute myocardial infarction (AMI). We present a case of a 44-year-old male with inferior ST elevation myocardial infarction (STEMI) complicated by VSR with cardiogenic shock, who underwent a life saving operation 5 days after the onset of AMI. Due to residual flow through the ventricular septum and the development of ventricular aneurysm the patient underwent reoperation 15 weeks later, but still residual VSR remained. During the follow-up we observed remodeling of the left ventricle which responded to pharmacological treatment. The authors discuss risk factors, therapeutic options and complications related to AMI-associated VSR.